2014
DOI: 10.1007/s00338-014-1246-y
|View full text |Cite
|
Sign up to set email alerts
|

A paradoxical reef from Varadero, Cartagena Bay, Colombia

Abstract: Coral reefs in the Bay of Cartagena, Colombia, have been heavily disturbed by anthropogenic perturbations since the founding of Cartagena in 1533. A prominent perturbation was the construction of Canal del Dique, a channel built by the Spaniards to shorten the access to the Magdalena River, a major waterway used by Colombian authorities for colonization and later for commercial purposes. Canal del Dique turned the clear waters of Cartagena Bay into a seasonally fluctuating, highly turbid, and eutrophied body o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 1 publication
0
19
0
1
Order By: Relevance
“…The existence of Varadero, a "paradoxical reef" (López-Victoria et al, 2015), is a call for scientists and managers to start looking in unexpected places for similar reefs. More importantly,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The existence of Varadero, a "paradoxical reef" (López-Victoria et al, 2015), is a call for scientists and managers to start looking in unexpected places for similar reefs. More importantly,…”
Section: Discussionmentioning
confidence: 99%
“…In order to supplement the brief, general description of Varadero Reef reported by López-Victoria et al (2015), detailed geomorphological and biological surveys were performed between 2014 (March) and 2015 (March and October). During the March 2015 field trip, Reef's geographic extent was assessed by two researchers diving along the border of the Reef with a GPS, recording in tracking mode, attached to an accompanying buoy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This premise is reinforced by other studies in the Indian and Pacific Oceans (van Woesik et al, 2012;Cacciapaglia and van Woesik, 2015), which observed turbid nearshore environments as climate change refuges with turbidity mitigating high-temperature bleaching. In addition, there have been reports of healthy coral reefs (high coral cover) in the Caribbean in areas of high anthropogenic inputs (García-Sais et al, 2014;López-Victoria et al, 2015).…”
Section: Changes In Coral Compositionmentioning
confidence: 99%